MENINGKATKAN KETERAMPILAN MENYIMAK CERITA FABEL MELALUI MODEL PAIRED STORYTELLING MELALUI MEDIA WAYANG KARTUN DI KELAS II MI BPPI CISAAT DENGAN TEKNIK PROJECT BASE LEARNING (PJBL) - Nurkaidah; Dwi Kartika Susanti (STISIP Widyapuri Mandiri, 2023)
This study was conducted to overcome the problem of lack of enthusiasm and concentration of students when the teacher explains in front of the class in class II MI BPPI Cisaat. The purpose of the study was to improve listening skills to fable stories through the Paired Storytelling model using cartoon puppet media with the application of Project Based Learning (PjBL) techniques in the class. This study involved 26 students (12 boys and 14 girls) as subjects. Data were collected through observation methods and written tests. The results showed an increase in students' listening skills. In the first cycle, the average class score was 69 with a percentage of listening skills completeness of 70.91% (sufficient category) and learning outcomes completeness of 61.5% (unfinished category). In the second cycle, with the application of the Paired Storytelling model using cartoon puppet media and Project Based Learning (PjBL) techniques, the average class score increased to 82. The percentage of listening skills completeness increased to 81.73% (good category) with a percentage of learning outcomes completeness of 84.6% (complete category). Comparative analysis between the results of the first and second cycles shows a significant improvement in students' listening skills in dealing with fable stories in class II MI BPPI Cisaat. This research encourages a better and deeper understanding of listening skills through the implemented learning model.